One Month Follow-up of Haemostatic Variables in Patients Undergoing Aortocoronary Bypass Surgery - Mannucci, L; Gerometta, P S; Mussoni, L; Antona, C; Parolari, A; Salvi, L; Biglioli, P; Tremoli, E (Thrombosis and Haemostasis, 1995)
It is already known that activation of the coagulation and fibrinolytic system occurs in patients undergoing cardiopulmonary bypass (CPB). We have thus studied twenty patients (10 treated with aprotinin during CPB and 10 untreated) both during the intraoperative period and during thirty days follow up. In untreated patients D-dimer levels increased 4-fold during CPB and the levels were above baseline for the whole follow up (p<0.0001). D-dimer levels were reduced in aprotinin treated patients in comparison to untreated patients (p = 0.0172); levels then gradually increased to the values of the untreated patients over the following 24 h later and remained higher during the thirty day follow up. The behavior of haemostatic variables in the 24 h after CPB did not vary between untreated and aprotinin treated patients. In particular, five minutes after protamine sulphate administration, levels of F1 + 2 and TAT rose significantly (p = 0.0054, p = 0.0022 respectively), whereas fibrinogen significantly decreased (p<0.0001) and PAI-1 antigen levels were reduced. Two days after CPB the concentrations of F1 + 2 and TAT lowered, whereas fibrinogen and PAI-1 antigen levels increased. On the 5th, 8th and 30th days after CPB, F1 + 2 and TAT levels remained higher than those reported at baseline in both groups of patients, whereas fibrinogen levels increased over basal levels in aprotinin treated patients only.Thus, in addition to the activation of the coagulation and fibrinolytic system occurring during the intraoperative period, in patients undergoing CPB, there are alterations of haemostatic variables up to thirty days from surgery.